Myth, the hero and historical resistance in La guerra silenciosa, by Manuel Scorza - Salazar Mejía, Nécker (2019)
In “The Silent War”, Manuel Scorza addresses the rebellion of peasant leaders in the communities of central Peru against transnational capitalism, landowning power and the justice system. In this struggle, myth plays a decisive role, lending weight to the project of the Scorzian hero and guiding the quest for justice in the Andean world. In the portrayal of the characters, we find underlying mythical resonances associated with the messianism and redemption of the Indians, that have as their backdrop notions associated with an Andean utopia. The aim of this paper is to address the function of myth in the Scorzian oeuvre and its articulation through the deeds of the leaders of the peasant masses, in their search for justice. The paper proposes that, in the work of Scorza, myth is articulated through the perspective of the vanquished, as a device for reversing the injustice of the order imposed by hegemonic power in the Peruvian Andes.